Marine anomurans (Decapoda) from the non-consolidated sublittoral bottom at the southeastern coast of Brazil - Fransozo, Adilson [UNESP]; Fernandes-Goes, Lissandra C.; Fransozo, Vivian [UNESP]; Goes, Joao M.; Cobo, Valter J.; Teixeira, Gustavo M. [UNESP]; Gregati, Rafael A. [UNESP] (Brill Academic Publishers, 2011)
The present study assessed the composition and abundance of species of Anomura at the southeastern coast of Brazil. Sampling was carried out monthly from January 1998 to December 1999, in three regions of Ubatuba: Ubatumirim Bay, Ubatuba Bay and Mar Virado Bay, using a fishing boat equipped with two double-rigged nets. Four transects were defined at depths of 5, 10, 15, and 20 meters in each bay. Two additional transects were defined perpendicular to the beach: one in a sheltered area and the other in an area exposed to wave action. A total of 6356 specimens of anomurans representing 15 species and 9 genera of 3 superfamilies (11 Paguroidea, 1 Hippoidea, and 3 Galatheoidea) was recorded. Paguristes robustus was recorded for the first time from the São Paulo State coast. Dardanus insignis was the most abundant species, followed by Loxopagurus loxochelis and Porcellana sayana. The high abundance of P. sayana may be related to the presence of D. insignis and Petrochirus diogenes, because this porcellanid crab lives inside the shells occupied by these hermit crabs. Species richness varied among the bays and transects, but the highest values were observed at the exposed and sheltered areas. The highest abundance of anomurans was recorded at a depth of 20 m during winter in the bays Mar Virado and Ubatuba. The anomuran species comprised 75% of the total number previously recorded from coastal non-consolidated bottoms of São Paulo. We therefore infer that this region affords favourable biotic and abiotic conditions for the settlement and maintenance of a large number of species of Anomura.